Comparison of tamsulosin hydrochloride versus tamsulosin hydrochloride and deflazacort in relieving postoperative urinary retention in patients undergoing transurethral resection of prostate: a prospective randomized controlled trial in a tertiary care centre - Nagabhairava, Manu K.; Puvvada, Sandeep; T., Manasa; Reddy, Mani C.; Javali, Tarun; D., Ramesh (International Journal of Research in Medical Sciences, 2024)
Background: Benign prostatic hyperplasia (BPH) is common amongst the elderly. Even after transurethral resection of prostate (TURP), retention of urine may persist in some leading to significant morbidity adversely affecting the quality of life. The role of alpha blockers in this situation as a combination is unclear. The present study was conducted to evaluate and compare the efficacy of tamsulosin versus tamsulosin and deflazacort in relieving the postoperative retention of urine following TURP. Methods: After obtaining ethics approval and written informed consent, 72 patients satisfying the eligibility criteria were included. After TURP, patients with urinary retention following catheter removal were randomized into group A (tamsulosin hydrochloride) and group B (tamsulosin hydrochloride and deflazocort). baseline international prostate symptom score (IPSS) score was done to assess quality of life and findings of radiological investigations were noted. Thereafter, medical therapy was done as per assigned group and postoperative findings were documented and analyzed. Results: Both the groups were similar in terms of demographic characteristics and baseline characteristics. The relief of symptoms was significantly more in group B along with lower IPSS score and residual volume. Conclusions: We recommend addition of deflazacort to tamsulosin hydrochloride as medical therapy for the management of postoperative retention of urine (POUR), especially following TURP.